An Investigation on Cracking of Glasspanes Due to Air Overpressure - A J. Prakash; M D. Nabinllah; Bharat B. Dhar (International Society of Explosives Engineers, 1994)
The study is an approach made in simulating air overpressures induced by surface blasting from those produced during gallery blasting in the laboratory, and experiments conducted on a portable window with a view to establish the sound pressure Level (SPL) for cracking of window glasspanes.